2021
DOI: 10.1002/tkm2.1278
|View full text |Cite
|
Sign up to set email alerts
|

Immunological validation of the pharmacological and anti‐allergic action of glycyrrhetinic acid from Glycyrrhizae Radix

Abstract: Aim Glycyrrhetinic acid (GA) is an important and active metabolite derived from glycyrrhizin (GL) in Glycyrrhizae Radix (GR) that induces anti‐allergic, anti‐inflammatory, anti‐oxidant, anti‐viral, and anti‐microbial effects in vivo. To validate these beneficial actions of GA as an active compound of GR in vivo, we prepared a monoclonal antibody against GA. Methods The monoclonal antibody, mAb6D6, was prepared and evaluated for cross‐reactivity with GA and its analogs using competitive enzyme‐linked immunosorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…We are currently investigating which of the 10 constituents of JTT are effective crude drugs through their effect on the murine model of CHS with the adoptive transfer experiment. We have already reported that a hot water extract of Glycyrrhiza Radix and its major ingredient, glycyrrhizin, shows the anti-allergic effects on a murine model of CHS [43,44]. Moreover, there are some reports that paeoniflorin, a major ingredient of Paeoniae Radix, inhibited inflammatory responses in mice with allergic contact dermatitis induced by DNCB [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…We are currently investigating which of the 10 constituents of JTT are effective crude drugs through their effect on the murine model of CHS with the adoptive transfer experiment. We have already reported that a hot water extract of Glycyrrhiza Radix and its major ingredient, glycyrrhizin, shows the anti-allergic effects on a murine model of CHS [43,44]. Moreover, there are some reports that paeoniflorin, a major ingredient of Paeoniae Radix, inhibited inflammatory responses in mice with allergic contact dermatitis induced by DNCB [45][46][47].…”
Section: Discussionmentioning
confidence: 99%